Characterisation of ESBL/AmpC-Producing Enterobacteriaceae isolated from poultry farms in Peninsular Malaysia. (15th December 2022) - Tan, Hui-Shee; Yan, Pan; Agustie, Hollysia Alda; Loh, Hwei-San; Rayamajhi, Nabin; Fang, Chee-Mun
Abstract: Extended-spectrum beta-lactamases (ESBLs) and AmpC beta-lactamases (AmpCs)-producing Enterobacteriaceae have been increasingly reported and imposing significant threat to public. Livestock production industry might be the important source for clinically important ESBL-producing Enterobacteriaceae . This study aims to investigate the resistance profile, phenotypic ESBL production, beta-lactamase genes, virulence factors and plasmid replicon types among 59 Enterobacteriaceae strains isolated from poultry faecal samples in Malaysia's commercial poultry farm. There were 38.7% and 32.3% of E. coli resistant to cefotaxime and cefoxitin respectively while Klebsiella spp. demonstrated resistance rate of 52.6% to both mentioned antimicrobials. Majority of the E. coli isolates carried bla TEM and bla CMY-2 group . bla SHV was the most prevalent genes detected in Klebsiella spp., followed by bla DHA and bla TEM . Resistance to extended spectrum cephalosporin in our isolates was primarily mediated by plasmid mediated AmpC beta-lactamase such as CMY-2 group and DHA enzyme. The CTX-M genes were found in two ESBL-producing E. coli . IncF, IncI1 and IncN plasmids were most frequently detected in E. coli and Klebsiella spp. The virulence factor including EAST1 and pAA were identified at low frequency. This study highlights the poultry as a reservoir of resistance and virulence determinants and prevalence of plasmids in Enterobacteriaceae might drive their dissemination.